The controlling interpersonal style in a coaching context: Development and initial validation of a psychometric scale - Bartholomew, K. J.; Ntoumanis, N.; Thøgersen-Ntoumani, C. (Journal of Sport & Exercise Psychology, 2010)
This article outlines the development and initial validation of the Controlling Coach Behaviors Scale (CCBS), a multidimensional self-report measure designed to assess sports coaches` controlling interpersonal style from the perspective of self-determination theory (Ryan & Deci, 2002). Study 1 generated a pool of items, based on past literature and feedback from coaches, athletes, and academic experts. The factorial structure of the questionnaire was tested using exploratory and confirmatory factor analyses across Studies 2 and 3. The final CCBS model in Study 3 comprised 4 factors (controlling use of rewards, conditional regard, intimidation, and excessive personal control) and was cross-validated using a third independent sample in Study 4. The scale demonstrated good content and factorial validity, as well as internal consistency and invariance across gender and sport type. Suggestions for its use in research pertaining to the darker side of coaching and sport participation are discussed.